(untitled) (Research, Society and Development, 2021)
Objective: To know the ethnobotanical and traditional use of barbatimão in the establishment of the wound healing process. Method: This is an integrative literature review, descriptive and with a qualitative approach. It was conducted in August 2019, with the following DeCS and MeSH descriptors, wound healing, woundsand injuries, Stryphnodendron astringens; interspersed by the Boolean operator AND. The search was conducted via the Capes Periodicals Portal, in the following databases: MEDLINE, LILACS, BDENF, CINAHL, COCHRANE LIBRAY, IBECS, SCIENCE DIRECT. After conducting the search in the databases, 15 articles were obtained, which according to the application of inclusion and exclusion criteria, remained only, three studies that met the research object under study. Results: The results pointed out that the studies have in common the realization of ethnobotanical surveys, highlighting the traditional use through popular knowledge, of several plant species, and among them, the barbatimão presented a great prominence among the selected studies, mainly regarding the use as a healing element for skin wounds. Final considerations: The use of this plant is still little diffused in the scientific environment in the process of healing wounds and injuries, even with the popular knowledge about its applicability, the studies deal little with the preparation, concentration, time of use, interactions with other medications, and adverse effects on barbatimão, making it difficult to evaluate its therapeutic efficacy.